ENHANCING SUSTAINABLE LOCAL DEVELOPMENT THROUGH COLLECTIVE ORGANIZATIONAL ENGAGEMENT AND ENTREPRENEURSHIP DRIVEN ACTION SPIRIT - Palin Phoocharoon, (PEOPLE: International Journal of Social Sciences, 2024)
Designing a comprehensive theory of collective organizational engagement with entrepreneurship theory on the resource management model to achieve local development in impoverished places becomes an exciting challenge of the high potential organization. Proposing one intervention to address those concerns, which is the demand of high-growth entrepreneurship to shift the focus rather from economic growth by investing on the building infrastructure to investing on human and social capital. To achieve those challenging objectives, firms are not only focusing on economic growth but also fostering social inclusion, cultural diversity, and environmental sustainability across generations. Those strategic move and actions requires the exclusive pursuit support of new paradigm of entrepreneurship spirit.